PVP-assisted thermal annealing of thin Au layer for creation of effective and reproducible SERS substrates - Milyutina (Miliutina) E. V. Elena Vadimovna; Kalachyova E. Evgeniya; Burtsev V.; Postnikov P. S. Pavel Sergeevich; Elashnikov R. Roman; Svorcik V. Vaclav; Lyutakov O. Oleksy (2019, 2019)
Title screen